2021
DOI: 10.12998/wjcc.v9.i22.6287
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of secreted protein acidic and rich in cysteine in the diffuse large B-cell lymphoma

Abstract: BACKGROUND Secreted protein acidic and rich in cysteine (SPARC) is an extracellular matrix-associated protein. Studies have revealed that SPARC is involved in the cell interaction and function including proliferation, differentiation, and apoptosis. However, the role of SPARC in cancer is controversial, as it was reported as the promoter or suppressor in different cancers. Further, the role of SPARC in lymphoma is unclear. AIM To identify the expression and significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Single DLBCL cells play a role in adhesion to adjacent mesenchymal stromal cells and extracellular matrix (Dus-Szachniewicz et al, 2018). Pan et al reported the extracellular matrix-associated protein SPARC was highly expressed in DLBCL and might be a favorable prognostic biomarker for DLBCL (Pan and Liu, 2021). In addition, fibroblast and extracellular matrix components which represent stromal genetic signatures are associated with good survival in DLBCL (Haro and Orsulic, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Single DLBCL cells play a role in adhesion to adjacent mesenchymal stromal cells and extracellular matrix (Dus-Szachniewicz et al, 2018). Pan et al reported the extracellular matrix-associated protein SPARC was highly expressed in DLBCL and might be a favorable prognostic biomarker for DLBCL (Pan and Liu, 2021). In addition, fibroblast and extracellular matrix components which represent stromal genetic signatures are associated with good survival in DLBCL (Haro and Orsulic, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…e multivariate Cox analysis revealed that lower FAK expression may be an independent predictor of poor disease outcomes [19]. Furthermore, another study reported that leukocyte transendothelial migration, ECMreceptor interaction, and focal adhesion were implicated in the development of diffuse large B-cell lymphoma [20].…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, albumin is known to pass through the endothelial barrier at the tumour site via albumin-binding proteins such as Gp60. 39,40 Since tumour tissues consume a great deal of nutrients and energy during the rapid growth of tumour cells, albumin appears to be taken up as a source of nutrients via albumin-binding proteins. 40 Therefore, CO-HemoAct-DOX, whose surface was covered by albumin, with a core haemoglobin load (CO), could be effectively delivered to tumour tissues by enhancing the EPR effect and uptake via Gp60, leading to high anti-tumour activity.…”
Section: Anti-tumour Effect and Tumour Distribution Of Co-hemoact-dox...mentioning
confidence: 99%